Evaluation Of Degree Of Overconservatism In Api Shaft Friction Of Piles In Marine Sand Of The Arabian Gulf - Ahmed H. Bukhary; Naser A. Al-Shayea (Deep Foundations Institute)
The objective is to assess the overconservatism in the parameters used for designing offshore piles. Methodology includes analysis of shaft friction data obtained from more than five different locations in the Arabian Gulf, consisting of 40 piles to depths up to 86 m. Reports were collected for both the dynamic pile monitoring system (DMS) and their corresponding geotechnical reports based on the American Petroleum Institute (API). The values of shaft capacity for the sand layers were analysed by comparing those based on API to the corresponding DMS values. Results of the comparison of the data from these reports showed that the pile design parameters obtained using API guidelines is generally smaller than that measured by DMS. The difference is presented in terms of an overconservative factor (OCF) which is adjusted based on statistical nonparametric test performed on the two data sets. The adjusted OCF were found to be 1.79 and 2.00 for carbonate sand at (loose to medium dense) and (dense to very dense) conditions, respectively. The corresponding values for silica sand were only 1.2 and 1.06. In conclusion, based on the evaluation conducted for data from these reports, the API shaft friction is overconservative for carbonate sand. The API shaft friction for piles in sand can be increased by multiplying it by the adjusted OCF.